Investigation of the Skin Anti-photoaging Potential of Swertia chirayita Secoiridoids Through the AP-1/Matrix Metalloproteinase Pathway by Molecular Modeling - Pathomwat Wongrattanakamon (2018)
© 2018 Springer Science+Business Media, LLC, part of Springer Nature Secoiridoids are bioactive compounds, which are present in plants and exhibit anti-inflammatory activity. In this work, to understand the structural basis of five secoiridoids; amarogentin, amaroswerin, gentiopicrin, sweroside, and swertiamarin for potent inhibitors of the target proteins associated with the collagen degradation pathway, namely MMP-1, MMP-3, MMP-9 and transcription factor AP-1, molecular docking, binding mode modeling, and MD simulations were carried out. The binding inhibitory effects of the secoiridoids were screened on these proteins. The obtained results in terms of binding conformation, binding free energy, protein–ligand interaction profile, structural flexibility, and binding energy decomposition of the secoiridoid inhibitors were elucidated. The molecular modeling clarified inhibitory effect on account of the five secoiridoids towards all three Matrix metalloproteinases (MMPs). Moreover, amarogentin and gentiopicrin may interfere with gene expression via binding to AP-1. Among all screened secoiridoids, amarogentin and gentiopicrin exhibited an interesting binding affinity to the MMPs and AP-1. The results suggest that amarogentin has the highest potential for application as an anti-aging agent with the MMP inhibitory and anti-transcriptional activities, even though further studies are needed to determine the anti-aging effect in vitro, in vivo and by clinical evaluation.